Síntese de derivados do fulereno-C60 - Leandro Jose dos Santos (2010)
Presently, C60 fullerene and its derivatives are of great importance in chemistry, mainly due to their physical properties and biological activities. One of the main problems related to C60 is its low solubility in the commonly used solvents, which limits its application. Aiming to study their physicochemical properties, 17 new C60 derivatives with appropriate solubility were synthesized in this work through a cyclopropranation reaction and functionalized with carbohydrates, pyridines, tetrazoles, and oxadiazole. Considering that the azole derivatives presented good solubility in organic solvents and aiming for a possible application of these compounds, two studies of their physico-chemical properties were performed: the investigation of the photosensibility of these derivatives in solution and the study of their electrochemical properties. The photosensibility for conversion of oxygen triplets into reactive oxygen species (ROS) was investigated by electron paramagnetic resonance. The results suggest that ROS were produced in an azole derivative solution under laser illumination. These derivatives, therefore, are potential photosensitizers and may have a topical use in photodynamic therapy. The analysis of the azole derivatives by cyclic voltammetry has shown that the electrochemical properties of the C60 sphere were not significantly altered by its functionalization. Therefore, these derivatives are promising candidates for the construction of a photovoltaic cell. The pyridinium salts and the synthesized tetrazole salts presented good solubility in DMSO and in a mixture of DMSO/H2O, which makes the future investigation of the biological and photophysical properties of their compounds possible. On the other hand, the insolubility of carbohydrate-containing fullerene derivatives is an obstacle to their practical application.